Best Answer

1) y - 7y = 36 -6y = 36

y = -6

We know that, y = 3x

-6 = 3x

x= -2

Conclusion, y= -6, x = -2

Q: 3x - 7y equals 36 and y equals 3x?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

y-3x+6y=12 7y=3x+12 y=3x/7 +12/7

3

Where an equation is presented in this form then convert it to the standard slope intercept format of y = mx + c. The value of m is the slope. 3x - 7y = 14 7y = 3x - 14 y = 3/7x - 2 The slope is therefore 3/7.

3x = 7y - 2 (subtract 3x and 7y to both sides of the first equation)9y = 4x + 1-7y = -3x - 2 (multiply by 4 each term of both sides of the first equation)9y = 4x + 1 (multiply by 3 each term of both sides of the second equation)-28y = -12x - 827y = 12x + 3 (add both equations)-y = -5 (multiply by -1 both sides)y = 53x = 7y - 2 (substitute 5 for y)3x = 7(5) - 23x = 33 (divide both sides by 3)x = 11Thus, the solution of the given system of the equations is x = 11 and y = 5.

put both equations in standard form y - 3x = -5 (equation 1) -7y + 21x = 35 (equation 2) multiply equation 1 by 7 (this is done so either one of your variables will cancel... if both variables cancel then these lines are parallel) 7y - 21x = -35 -7y + 21x = 35 0 = 0 therefore your lines are parallel

Related questions

7y+3x-21 =0 7y = -3x+21 y = -3/7x+3 The y intercept is 3

3x + 7y = 14Subtract 3x from each side:7y = -3x + 14Divide each side by 7:y = -3/7 x + 2

T = 3x + 7y; x = 4; y = 6T = 3x + 7y (substitute 4 for x, and 6 for y)T = 3(4) + 7(6) = 12 + 42 = 54

3x+y=5(4x-7y)=-10 3x+y=20x-35y=-10 -3x -3x y=17x-35y=-10 -y -y 17x-36y=-10 sorry but that's as far as i could get :(

3x + 7y = 3*x + 7*y = 3*6 + 7*4 = 18 + 28 = 46

9x-9y = 36 => x-y = 4 3(-y+x = 4) 7y-3x = -14 Multiply all terms in the top equation by 3: -3y+3x = 12 7y-3x = -14 Add both equations together: 4y = -2 Divide both sides by 4: y = -0.5 Substitute the value of y into the original equations to find the value of x: x = 3.5 and y = -0.5

4

y-3x+6y=12 7y=3x+12 y=3x/7 +12/7

y = -1 and x = -3

Put in this form. Y = mX + c3X - 7Y = 8- 7Y = - 3X + 8Y = (3/7)X - 8/7===========Y intercept = - 8/7-----------------------

x=0 and y=12\7

y=5.